Bone mineral density in asthmatic patients on inhaled corticosteroids in a developing country - Kuan, Yeh Chunn; How, Soon Hin; Abd. Aziz, Azian; Chong, Kin Liam; Ng, Teck Han; Abdul Rani, Mohammed Fauzi (Medknow Publications, 2012)
INTRODUCTION: Prolonged use of oral conicostero,as ,s a risk factor for osteoporosis. However, the effect of inhaled corticos-teroids (CS) on bone mineral density (ENID) of asthmatic patients remains controversial. OBJECTIVES. We aimed to determine the prevalence of osteopenia and osteoporosis in our patients with asthma receiving ICSs for more than one year compared with patients who did not have asthma and to determine the risk factors for osteopenia and osteoporosis among the asthmatic patients. METHODS: This was a cross-sectional study conducted from August 2007 to July 2009. Asthmatic patients aged la years and older who had been on ICS for at least one year and a control group of subjects not on ICS were included. BMD was measured using DEXA (dual energy X-ray absorptiometry) scan. The WHO classification of T•scOreS for osteopenia and osteoporosis were used. RESULTS, A total 01 143 subjects were recruited (69 asthmatics and 74 control subjects). T-scores of the spine, femur, and hip of the asthmatics vs the control subjects were mean, -0,72 VS -0 .57 (P = 0.98): median, -0.60 vs -0,80 (P=0 474), and mean, 0,19 vs 0.06 (P=0.275), respectively. T-scores of the spine, lemur, and hip showed significant negative correlation with age and significant positive correlation with body mass index (13M1), CONCLUSIONI The risk factors for osteoporosis and osteopenia among asthmatic patients were older age and lower BMI, but not the cumulative dose of ICS. Asthmatic patients on ICS have no added risk of osteoporosis or ostecpenia as compared with non-asthmatic subjects. Key words: Asthma, asthma, bone mineral density, inhaled corticosteroilds